Search for hadronic Decays of a light Higgs Boson in the radiative decay Y → γA0 - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review letters, 2011)
We search for hadronic decays of a light Higgs boson (A0) produced in radiative decays of an Υ(2S) or Υ(3S) meson, Υ→γA0. The data have been recorded by the BABAR experiment at the Υ(3S) and Υ(2S) center-of-mass energies and include (121.3±1.2)×106 Υ(3S) and (98.3±0.9)×106 Υ(2S) mesons. No significant signal is observed. We set 90% confidence level upper limits on the product branching fractions B(Υ(nS)→γA0)B(A0→hadrons) (n=2 or 3) that range from 1×10−6 for an A0 mass of 0.3 GeV/c2 to 8×10−5 at 7 GeV/c2.